Supervised versus non-supervised exercise in patients with recent myocardial infarction: A propensity analysis. (February 2016) - Coll-Fernández, Roser; Coll, Ramon; Muñoz-Torrero, Juan F Sánchez; Aguilar, Eduardo; Ramón Álvarez, Lorenzo; Sahuquillo, Joan Carles; Yeste, Montserrat; Jiménez, Pedro Enrique; Mujal, Abel; Monreal, Manuel; ,
Background: The influence of supervised versus non-supervised exercise training on outcome in patients with a recent myocardial infarction (MI) is controversial. Design: Longitudinal observational study. Methods: FRENA is an ongoing registry of stable outpatients with symptomatic coronary, cerebrovascular or peripheral artery disease. We compared the rate of subsequent ischaemic events (MI, ischaemic stroke or lower limb amputation) and the mortality rate in patients with recent MI, according to the use of supervised versus non-supervised exercise training. The influence of physical activity on outcomes was estimated by using propensity score method in multivariate analysis. Results: As of February 2014, 1124 outpatients with recent MI were recruited, of whom 593 (53%) participated in a supervised exercise training programme. Over a mean follow-up of 15 months, 25 patients (3.3%) developed 26 subsequent ischaemic events – 24 MI, one stroke, one lower-limb amputation – and 12 (1.6%) died. The mortality rate (0.15 vs . 2.89 deaths per 100 patient-years; rate ratio = 0.05; 95% confidence interval, 0.01–0.39) was significantly lower in supervised exercise than in non-supervised exercise patients. On propensity score analysis, the rate of the composite outcome was significantly lower in supervised exercise patients (1.80 vs . 6.51 events per 100 patient-years; rate ratio = 0.28; 95% confidence interval, 0.12–0.64). Conclusions: The use of supervised exercise training in patients with recent MI was associated with a significant decrease in the composite outcome of subsequent ischaemic events and death.